Clinical case of diagnosis of left ventricular non-compaction in a child - T.O. Kryuchko; S.M. Tanianska (Zaslavsky O.Yu., 2023)
Diseases of cardiovascular system in children present an extremely urgent problem nowadays. According to the latest epidemiological studies, there has been an increase by almost 3.2 % in congenital heart disease in Ukrainian children over the past 20-30 years. Left ventricular non-compaction belongs to a group of unclassified cardiomyopathies with undetermined prevalence. At the same time, based on literature, this pathology is characterized by a late diagnosis and very high mortality. In the pathogenesis of the disease, structural changes in the myocardium occur during the embryonic stage, leading to its abnormal development. Left ventricular non-compaction is considered a genetically heterogenous disease, which is inherited in an autosomal dominant pattern. The article deals with a clinical case of diagnosis and management of a child with left ventricular non-compaction, which demonstrates to general practitioners, pediatricians, and pediatric cardiologists the algorithm for diagnosing and managing patients with a rare disease in order to make earlier diagnosis, prevent complications, and preserve patient's life. The patient who has been suffered from pneumonia, complained of breathlessness and rapid fatigue during minor physical exertion was timely referred by the family doctor for consultation with a pediatric cardiologist. Laboratory and instrumental studies allowed to suspect a rare congenital heart disease - left ventricular non-compaction. Subsequently, the patient was regularly examined by cardiologists and cardiac surgeons, received protocol therapy, was registered in a state transplant registry, which allowed to wait for a donor with subsequent successful heart transplant surgery.